Energy losses of highly charged Arq+ ions during grazing incidence on tungsten surfaces - Xie, Zun; Luo, Xianwen (Frontiers in Physics, 2024)
In the present work, the energy loss of highly charged ion interacting with various tungsten surfaces was studied. Based on COBM, simulations involving trajectory calculations, energy loss, charge exchange processes, surface electron distributions etc. have been performed, focusing on the impact of electron density distributions on energy loss. Remarkably, the pronounced influence under the axial channeling of surfaces on ion energy loss are emphasized. The correlation between surface azimuthal angles and energy loss under uniform and inhomogeneity electron density distribution are analyzed. The more pronounced influence of electron density inhomogeneity on energy loss of ions at the higher energy-loss side was observed. Furthermore, the calculated energy-loss spectra of Ar 16+ ions grazing from a graphite surface agree reasonably with experiment. The findings play a vital role in probing the surface structure of crystals.